Editorial - Jolanta Drzewiecka; Katharina Lobinger; Mike Meißner (Studies in Communication Sciences, 2023)
The third and last issue of the year offers a diversity of communication topics. The General Section includes a study of parasocial relations with media characters and an analysis of COVID-19 rhetoric in Iran. The Thematic Section presents a rich discussion of issues and processes involved in the persistence of “old media.” Diverse topics are also presented in the Community Section including a summary of the SACM award winning dissertation and an introduction to DOCA. Finally, the contributions to the Book Review Section discuss books on Internet memes and the influencer industry. Before our more detailed overview, we are pleased to present an important next step for SComS. SComS is evolving toward Open Data and Open Research. Since 2017, SComS has been published as a platinum open access journal. One notable feature is the journals’ multilingual nature. For authors, the online first publication of articles is particularly advantageous, enabling the timely publication of accepted contributions. With these features, SComS has positioned itself as a dynamic and innovative journal in the European journal landscape. However, the step toward Open Data and Open Research has not been fully embraced yet.